Biotechnology on biopolymer in automotive interiors - Md Amin, Naqibah Solehah; Mohd Fauzi, Noor Akhmazillah; Mohamed, Elizah (Penerbit UTHM, 2022)
Biopolymers are renewable resourcederived polymers that attract interest as environmentally sustainable resins, since they are manufactured without relying on fossil fuel energy. The application of polylactic acid (PLA) and other biopolymers in the automotive sector (especially indoors) needs the products to meet the quality requirements such as high strength, low level of sunlight disruption, abrasion resistance, high longevity and high fire resistance. Owing to the fact that injection molding produces products with high dimensional tolerances at short cycle times and results in lower costs, hence the production techniques of polymer is crucial. In recent years biofibre-reinforced PLA composites have been of considerable concern. By combining a biodegradable matrix with biofibre reinforcement a biocomposite, a completely biodegradable material, is literally feasible. We may also look forward to ambitious R&D in the production of materials that are bio-degradable over those manufactured from polyester as its reprocessing which prove costlier than the disposal and composting of items such as seats manufactured from PLA fabrics.